FERN: is it possible to conduct a randomised controlled trial of intervention or expectant management for early-onset selective fetal growth restriction in monochorionic twin pregnancy – protocol for a prospective multicentre mixed-methods feasibility study - Kerry Woolfall; Jamie J Kirkham; Jane Sandall; Mariana Popa; Enrico Lopriore; Mark Turner; Shakila Thangaratinam; Aris T Papageorghiou; Andrew Sharp; Lawrence Impey; Andy Healey; Jessica Mendoza; et al. (BMJ Open)
Introduction Selective fetal growth restriction (sFGR) in monochorionic twin pregnancy, defined as an estimated fetal weight (EFW) of one twin <10th centile and EFW discordance ≥25%, is associated with stillbirth and neurodisability for both twins. The condition poses unique management difficulties: on the one hand, continuation of the pregnancy carries a risk of death of the smaller twin, with a high risk of co-twin demise (40%) or co-twin neurological sequelae (30%). On the other, early delivery to prevent the death of the smaller twin may expose the larger twin to prematurity, with the associated risks of long-term physical, emotional and financial costs from neurodisability, such as cerebral palsy.When there is severe and early sFGR, before viability, delivery is not an option. In this scenario, there are currently three main management options: (1) expectant management, (2) selective termination of the smaller twin and (3) placental laser photocoagulation of interconnecting vessels. These management options have never been investigated in a randomised controlled trial (RCT). The best management option is unknown, and there are many challenges for a potential RCT. These include the rarity of the condition resulting in a small number of eligible pregnancies, uncertainty about whether pregnant women will agree to participate in such a trial and whether they will agree to be randomised to expectant management or active fetal intervention, and the challenges of robust and long-term outcome measures. Therefore, the main objective of the FERN study is to assess the feasibility of conducting an RCT of active intervention vs expectant management in monochorionic twin pregnancies with early-onset (prior to 24 weeks) sFGR.Methods and analysis The FERN study is a prospective mixed-methods feasibility study. The primary objective is to recommend whether an RCT of intervention vs expectant management of sFGR in monochorionic twin pregnancy is feasible by exploring women’s preference, clinician’s preference, current practice and equipoise and numbers of cases. To achieve this, we propose three distinct work packages (WPs). WP1: A Prospective UK Multicentre Study, WP2A: a Qualitative Study Exploring Parents’ and Clinicians’ Views and WP3: a Consensus Development to Determine Feasibility of a Trial. Eligible pregnancies will be recruited to WP1 and WP2, which will run concurrently. The results of these two WPs will be used in WP3 to develop consensus on a future definitive study. The duration of the study will be 53 months, composed of 10 months of setup, 39 months of recruitment, 42 months of data collection, and 5 months of data analysis, report writing and recommendations. The pragmatic sample size for WP1 is 100 monochorionic twin pregnancies with sFGR. For WP2, interviews will be conducted until data saturation and sample variance are achieved, that is, when no new major themes are being discovered. Based on previous similar pilot studies, this is anticipated to be approximately 15–25 interviews in both the parent and clinician groups. Engagement of at least 50 UK clinicians is planned for WP3.Ethics and dissemination This study has received ethical approval from the Health Research Authority (HRA) South West—Cornwall and Plymouth Ethics Committee (REC reference 20/SW/0156, IRAS ID 286337). All participating sites will undergo site-specific approvals for assessment of capacity and capability by the HRA. The results of this study will be published in peer-reviewed journals and presented at national and international conferences. The results from the FERN project will be used to inform future studies.Trial registration number This study is included in the ISRCTN Registry (ISRCTN16879394) and the NIHR Central Portfolio Management System (CPMS), CRN: Reproductive Health and Childbirth Specialty (UKCRN reference 47201).